Dimensions of knowledge management maturity in the university libraries / Noreen Natasha Azmee, Mohd Shamsul Mohd Shoid and Mohd Idzwan Mohd Salleh - Azmee, Noreen Natasha; Mohd Shoid, Mohd Shamsul; Mohd Salleh, Mohd Idzwan (Faculty of Information Management, 2023)
Knowledge is recognised as a critical resource, and managing knowledge is crucial in organisations. The benefits of knowledge management have been reviewed in much literature. This paper presents an overview of knowledge management, the maturity model, and the knowledge management maturity model. To the best of our knowledge, the amount of literature relating to knowledge management maturity is almost nonexistent in the field of libraries. Identifying this gap, the main goal of this paper is to discover knowledge management maturity dimensions, namely human capital, support from top management, organisational culture, leadership, and employee skills, towards innovation performance in university libraries.